2023
DOI: 10.21856/j-pep.2023.1.07
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cholecalciferol on the Sex Hormones Level and Serum Biochemical Indices in Rat Males With Experimental Gonadopathy

Abstract: The testicular deficiency, cryptorchidism, varicocele, endocrine pathologies are the main causes of men infertility. The internal diseases of testicles lead to fertility declining in the major part of cases which explains the importance of studying of gonadopathies᾿ methods of correction. In recent times, vitamin D is noted among remedies suitable for effective correction of reproductive system. The aim of investigation: to determine the sex hormones levels and biochemical indices in serum of rats’ males with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The obtained results are supported by the literature data on the histological structure of the testes and the submicroscopic architecture of Sertoli cells after the use of Serotonin hydrochloride [6,26]. Under the influence of Serotonin hydrochloride, the number of activated hormone-producing Leydig cells decreases, as observed in our study and reported in the literature, which leads to a decrease in the androgen status of the animals' bodies, and is confirmed not only indirectly by the test of crystallization of the prostate gland secretion (see Table 3) but also by a decrease in the level of male sex hormone associated with experimental gonadopathy [4].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The obtained results are supported by the literature data on the histological structure of the testes and the submicroscopic architecture of Sertoli cells after the use of Serotonin hydrochloride [6,26]. Under the influence of Serotonin hydrochloride, the number of activated hormone-producing Leydig cells decreases, as observed in our study and reported in the literature, which leads to a decrease in the androgen status of the animals' bodies, and is confirmed not only indirectly by the test of crystallization of the prostate gland secretion (see Table 3) but also by a decrease in the level of male sex hormone associated with experimental gonadopathy [4].…”
Section: Discussionsupporting
confidence: 85%
“…Notes: 1 -Statistically significant differences compared to the control group, p<0.05; 2 -statistically significant differences compared to the S group, p<0.05; 3 -statistically significant differences compared to the S+vit. D 3 group, p<0.05; 4 -statistically significant differences compared to the S+Tr group, p<0.05.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations